Peer effect in mergers and acquisitions for green innovation - Yue Gu; Wenwu Xie; Xiaoxia Qian; Jiamin Lv (Journal of Innovation & Knowledge)
This paper investigates the existence and moderating mechanisms of the peer effect in mergers and acquisitions for green innovation (GIM&As). Using Chinese GIM&A data from 2010 to 2023, we find that there is peer effect in GIM&As. In other words, a firm’s GIM&A decisions will be affected by its peers’ GIM&As. More importantly, we uncover the novel mechanisms of a firm’s internal and external factors on the GIM&A peer effect. As for internal factors, a firm with higher ESG performance tends to adopt similar GIM&A strategies as its peers because it has more pressure to maintain its green reputation to sustain the competitive advantage. Moreover, higher managerial ability enables firms to make decisions more independently, rather than blindly imitating their peers’ GIM&As without considering their own characteristics and long-term development objectives. As for external factors, increasing environmental policies will weaken the GIM&A peer effect among firms by improving information sufficiency. Meanwhile, the GIM&A peer effect harms firms’ business performance because it may lead firms to initiate irrational deals that are either beyond their developmental needs or undertaken without adequate preparation. Our study provides convincing evidence and valuable advice for both firms and policymakers and helps them to reduce irrational imitations, thus better achieving the green innovation goals.